TINDAKAN KEMOTERAPI DENGAN TINGKAT KECEMASAN PADA KLIEN KANKER DI RUMAH SAKIT GRANDMED LUBUK PAKAM TAHUN 2021 - Kuat Sitepu; Adi Arianto; Luci Riani Br Ginting; Henni Dawati Damanik (JURNAL PENGMAS KESTRA (JPK), 2021)
Chemotherapy is a treatment process that uses antineoplastic preparations with the aim of killing cancer cells and slowing the growth of cancer cells by disrupting cellular function and reproduction. Research objectives: To determine the relationship between chemotherapy and anxiety levels in cancer clients at Grandmed Lubuk Pakam Hospital in 2021. Research methods: This study used a quantitative research design with the type of analytical survey. This study used a cross-sectional design, which is a type of observational study that analyzes data from a population. the research results obtained p value = 0.00. It means that the p value <0.05, then there is a relationship between chemotherapy measures and anxiety levels in cancer clients at Grandmed Lubuk Pakam Hospital in 2021. Conclusion: chemotherapy will provide different levels of anxiety for each patient undergoing it, depending on their attitude to accept the disease. as well as the existing knowledge about cancer that will be treated by chemotherapy. Suggestion: For Research Sites: It is hoped that it can add insight to other nurses to further maximize the actions to be taken